Sunscreen Activity of α -mangostin from the Pericarps of Garcinia mangostana - Liandhajani, Maria Immaculata Iwo, Sukrasno, Andreanus A. Soemardji, Muhammad Hanafi (Journal of Applied Pharmaceutical Science, 2013)
A sunscreen active compound has been isolated from the ethanol extract of Garcinia mangostana Linn (Clusiaceae). The ethanol extract was fractionated by liquid liquid extraction with n-hexane, methylene chloride and ethyl acetate, followed by further fractionation and purification using column chromatography on silica gel and gradient elution with combinations of n-hexane and ethyl acetate. Isolation and fractionation was guided by sunscreen activity assay. One of the active compounds was identified as αmangostin based on LC-MS and NMR Spectroscopy. The SPF value of the isolated α –mangostin at 50 and 100 ppm were 21.76 and 37.18, respectively and were much higher than the SPF values of the fractions obtained by liquid-liquid extraction.
Keywords: &alpha; -mangostin, Garcinia mangostana Linn, sun